Health status and health care services in Uttar Pradesh and Bihar: A comparative study - Manjaree Anand (Wolters Kluwer Medknow Publications, 2014)
Background: India's growth hype and dream of emerging as an economic superpower are being challenged today, among other things, by its failure to foster an inclusive growth path and provide to bulk of its population basic amenities of education and health. There exists great inequality at interstate and intrastate level in terms of the key components of human development-health and education. Aims: The present work attempts to measure the extent of the inequality in health status and health care services in the two most populous states of India namely Uttar Pradesh and Bihar. Materials and Methods: A detailed analysis of interdistrict and interregion disparity in health status and health care in the two states has been done using secondary data from Annual Health Survey (2011) and Statistical Diary (2011). Composite indices of health status and health services have been developed using Maher's normalization technique and principal component analysis. Inequality measures like co-efficient of variations have been used to measure the relevant disparities in the two states and explain the reason thereof. Results: The work shows low overall health status and wide interdistrict and interregion health disparity in the two states with lower disparity in Uttar Pradesh as compared to Bihar in terms of health status and relatively high disparity in health infrastructure. One startling fact is existence of very low and insignificant correlation between infrastructure and outcome. Conclusion: The study finds health status is influenced not only by health care facilities, but a number of other factors principally government's commitment and policies.